Electrostatic‐Assisted Liquefaction of Porous Carbons. (23rd October 2017) - Li, Peipei; Schott, Jennifer A.; Zhang, Jinshui; Mahurin, Shannon M.; Sheng, Yujie; Qiao, Zhen‐An; Hu, Xunxiang; Cui, Guokai; Yao, Dongdong; Brown, Suree; Zheng, Yaping; Dai, Sheng
Abstract: Porous liquids are a newly developed porous material that combine unique fluidity with permanent porosity, which exhibit promising functionalities for a variety of applications. However, the apparent incompatibility between fluidity and permanent porosity makes the stabilization of porous nanoparticle with still empty pores in the dense liquid phase a significant challenging. Herein, by exploiting the electrostatic interaction between carbon networks and polymerized ionic liquids, we demonstrate that carbon‐based porous nanoarchitectures can be well stabilized in liquids to afford permanent porosity, and thus opens up a new approach to prepare porous carbon liquids. Furthermore, we hope this facile synthesis strategy can be widely applicated to fabricate other types of porous liquids, such as those (e.g., carbon nitride, boron nitride, metal–organic frameworks, covalent organic frameworks etc.) also having the electrostatic interaction with polymerized ionic liquids, evidently advancing the development and understanding of porous liquids.